Variable effects of omaveloxolone (RTA408) on primary fibroblasts with mitochondrial defects - Zighan, Madleen; Arkadir, David; Douiev, Liza; Keller, Guy; Miller, Chaya; Saada, Ann (Frontiers in Molecular Biosciences, 2022)
Omaveloxolone (RTA408) is a second generation oleanane triterpenoid Nrf2 inducer with antioxidative and anti-inflammatory properties, and was reported to improve mitochondrial bioenergetics. It is currently being tested in medical trials for |Friedrich ataxia, genetic, multi-organ disease involving mitochondrial dysfunction. Thus, Omaveloxolone could potentially be beneficial for additional disorders involving mitochondrial dysfunction. To this end, we investigated its effect on primary fibroblasts derived from patients with mitochondrial complex1 deficiency, mitochondrial cytochrome oxidase deficiency and two recessive forms of Parkinson’s disease. Patients’ and control cells were incubated in the presence or absence of 50nM Omaveloxolone for 72h prior to measurements. Generally, growth on galactose medium and ATP production were unaltered. Mitochondrial membrane potential was slightly but significantly decreased while reactive oxygen species (ROS) production was variably decreased. Mitochondrial mass and mitochondrial DNA (mtDNA) contents were significantly increased in the patient’s cells. These results were partially confirmed by the results of oxygen consumption studies which disclosed increased maximal oxygen consumption rates in most cells and increased energy status in all treated cells. Further investigation is required to explore the precise effect of Omaveloxolone on mitochondrial function in disease.